MODAL SOSIAL DALAM PENGELOLAAN HUTAN DESA. STUDI KASUS DI DESA TANGKAHEN KABUPATEN PULANG PISAU: Social Capital in Village Forest Management. Case Study in Tangkahen Village, Pulang Pisau regency - I Nyoman Surasana; Agung Wibowo; Andri Efrya Wiranata (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
This study aims to determine the social capital of the community in village forestmanagement in the Tangkahen Village area, Pulang Pisau Regency. Data retrieval using thesnowball sampling method, which means the researcher stops looking for additionalinformation when there is no more new information. The results showed that the cumulativesocial capital characteristics of the Tangkahen Village community in managing their villageforest were in the high category. The role of each element of community social capital,namely: elements of trust, social norms, pro-active actions and concern for others and theenvironment are included in the high category, only the social network element has a role inthe medium category. Activities in village forest management that have been carried out areidentifying the potential of village forests, building tree houses for natural ecotourismpurposes and marketing (promotional) activities.Keywords: Social capital, village forest management, village forest